Anterior-Only Approach for Posttraumatic Subaxial Cervical Spine Spondyloptosis: A Case Report and Review of Literature - Raj Kumar; Suyash Singh; Kuntal Kanti Das; Arushi Kumar (Indian Journal of Neurosurgery)
Subaxial posttraumatic spondyloptosis is a rare entity with management dilemma in the literature. Various approaches have been discussed, but few reports focused on management plan and rationale. The authors reviewed the literature and reported a case of a 30-year-old woman presented with posttraumatic spastic quadriparesis. The patient had C6–7 spondyloptosis and was operated by anterior-only approach. There was improvement in both motor and sensory neurologic status. Surgical goals include vertebral realignment and stabilization. The authors conclude that anterior approach may be good enough if performed properly even if all three columns are involved.